Heat-resistant wafer cutting protective film and preparation method thereof

By adding heat-curing crosslinking agent and photo-crosslinking agent to the acrylate oligomer to form an interpenetrating network structure, the problem of insufficient heat resistance of acrylate UV-type viscosity-reducing glue is solved, and better heat resistance and peeling are achieved sexual regulation.

CN119242190APending Publication Date: 2025-01-03BEIJING SEQUENTIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411356727.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Acrylate UV viscosity-reducing glue has poor heat resistance during high-precision cutting, which is prone to deformation and residual glue, and cannot effectively fix and protect the wafer.

Method used

By adding a heat-curing crosslinking agent, the acrylate oligomer forms a crosslinked network structure and forms an interpenetrating network structure with the photo-crosslinking agent to improve heat resistance and reduce the residual glue after cutting, so as to make its peeling properties Easier to regulate.

Benefits of technology

It significantly improves the heat resistance of acrylate UV-reducing glue, reduces residual glue after cutting, and maintains initial viscosity, making peeling more easy to regulate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063823860000061
    Figure BDA0005063823860000061
  • Figure BDA0005063823860000062
    Figure BDA0005063823860000062
  • Figure BDA0005063823860000071
    Figure BDA0005063823860000071
Patent Text Reader

Abstract

The invention provides a heat-resistant wafer cutting protective film and a preparation method thereof. The heat-resistant wafer cutting protective film comprises a base material layer, a UV viscosity-reducing adhesive layer and a release film layer, and the UV viscosity-reducing adhesive layer comprises the following raw materials in parts by weight: 100 parts of an acrylate oligomer solution, 0.5-1 part of a thermal curing agent, 5-8 parts of a photo-crosslinking agent and 0.5-1.5 parts of a photoinitiator; the acrylate oligomer solution polymerization monomer comprises 20-40 parts of a soft monomer and 2-5 parts of a hard monomer; the thermal curing agent is a diglycidyl ether compound; the photo-crosslinking agent is prepared by reacting hyperbranched polyethyleneimine with an isocyanate-based unsaturated compound, and the molar ratio of primary amino on the hyperbranched polyethyleneimine to isocyanato on the isocyanate-based unsaturated compound is 1: (1-1.15). The thermocuring cross-linking agent enables the acrylate oligomer to form a cross-linked net structure, and the cross-linked net structure and the photocrosslinking agent are photocured to form another polymer network to interpenetrate to form an interpenetrating network structure, so that the heat resistance is improved, the residual glue is reduced, and the stripping property is easier to regulate and control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor manufacturing, and in particular relates to a heat-resistant wafer cutting protective film and a preparation method thereof. Background Art

[0002] With the continuous development of information technology and the semiconductor industry, the demand for various wafer-based devices is increasing. Viscosity-reducing film is a key material in wafer processing. During the cutting process of semiconductor wafers, the film provides a secure and protective barrier to prevent flying debris and breakage. After processing, the film is cured to facilitate easy removal of the workpiece, significantly reducing its adhesion and allowing the workpiece to separate from the substrate, allowing for further processing.

[0003] The anti-viscosity film is generally composed of a substrate film, an anti-viscosity adhesive, and a release film. Acrylic ester UV anti-viscosity adhesive has strong adhesion to semiconductor wafers and has been widely used in the semiconductor wafer processing industry. Acrylic ester UV anti-viscosity adhesive includes materials such as an acrylate copolymer base adhesive with cross-linking sites, a photopolymerizable multifunctional prepolymer or monomer, and a photoinitiator. When the wafer is processed, UV irradiation is applied to one side of the substrate film, and the unsaturated carbon-carbon double bonds in the acrylate copolymer base adhesive, the photopolymerizable multifunctional prepolymer or the monomer undergo cross-linking and curing, resulting in a large volume shrinkage. Many micropores are generated at the interface between the adhesive layer and the semiconductor wafer, greatly reducing the number of bonding points and the contact area, resulting in loss of adhesion. The probe then removes the cut wafer components from the anti-viscosity film.

[0004] For example, patent CN111303789B discloses an antistatic wafer cutting protective film, which includes a first antistatic layer, a substrate layer, a second antistatic layer, a viscosity-reducing layer, and a release film layer in sequence. The wafer cutting protective film prepared by combining a double-sided antistatic layer with a viscosity-reducing film material containing antistatic fillers avoids the phenomenon of residual adhesive that is easily generated during long-term storage or high-temperature conditions. At the same time, it can also improve the peel strength of the wafer cutting protective film before viscosity reduction and reduce the peel strength of the protective film after viscosity reduction, thereby improving the accuracy of fixation and picking efficiency. Patent CN112011287B discloses a dicing tape and a dicing chip bonding film, providing a dicing tape, etc., wherein the dicing tape has a substrate layer and an adhesive layer overlapping with the substrate layer, the adhesive layer comprising an acrylic polymer, the acrylic polymer comprising a constituent unit of a C9-C11 alkyl (meth)acrylate and a constituent unit of a hydroxyl (meth)acrylate, and the acrylic polymer comprising a constituent unit of a C9-C11 alkyl (meth)acrylate of not less than 40 mol% and not more than 85 mol%.

[0005] The above is a detackifying film made of acrylic UV detackifying adhesive to fix and protect the wafer during the cutting process, which can greatly improve the yield of the chip. However, high-precision cutting will generate a lot of heat energy. The heat resistance of acrylic UV detackifying adhesive is poor. After absorbing heat, the stiffness and strength of the detackifying adhesive decrease, and it is easy to deform and produce residual adhesive, which cannot play a good fixing and protective role.

[0006] Therefore, it is necessary to develop a wafer cutting protection film with excellent heat resistance. Summary of the Invention

[0007] In order to solve the above technical problems, the present invention provides a heat-resistant wafer cutting protective film and a preparation method thereof. By adding a thermosetting crosslinking agent, an acrylate oligomer forms a cross-linked network structure, which is then photocured with a photocrosslinking agent to form another polymer network to form an interpenetrating network structure, thereby improving the heat resistance of the acrylate UV viscosity-reducing adhesive, reducing the residual adhesive after cutting, and making its peeling properties easier to control, while not having an adverse effect on the initial adhesion.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A heat-resistant wafer cutting protective film comprises, from bottom to top, a substrate layer, a UV-resistant adhesive layer, and a release film layer. The UV-resistant adhesive layer comprises the following raw materials in parts by weight: 100 parts of an acrylate oligomer solution, 0.5-1 parts of a thermal curing agent, 5-8 parts of a photocrosslinking agent, and 0.5-1.5 parts of a photoinitiator. The acrylate oligomer solution is prepared by solution polymerization of 20-40 parts of a soft monomer, 2-5 parts of a hard monomer, and 10-15 parts of a hydroxy acrylic acid derivative. The thermal curing agent is a diglycidyl ether compound. The photocrosslinking agent is prepared by reacting a hyperbranched polyethyleneimine with an isocyanate-based unsaturated compound, and the molar ratio of the primary amine group on the hyperbranched polyethyleneimine to the isocyanate group on the isocyanate-based unsaturated compound is 1:1-1.15.

[0010] Furthermore, the solid content of the acrylate oligomer solution is 35-45 wt %.

[0011] The isocyanate-based unsaturated compound is selected from one or a combination of two or more of 4-(maleimido)phenyl isocyanate, 3-isopropenyl-α,α-dimethylbenzyl isocyanate, methacryloyl isocyanate, and 2-isocyanoethyl acrylate, preferably 4-(maleimido)phenyl isocyanate.

[0012] The hyperbranched polyethyleneimine has a number average molecular weight of 300-600 g / mol, an amine value of 18-21 mmol / g, wherein the molar proportion of primary amine is 35-45%, the molar proportion of secondary amine is 20-35%, and the molar proportion of tertiary amine is 20-35%.

[0013] The photocrosslinker is prepared by a method comprising the following steps:

[0014] Under an inert atmosphere, hyperbranched polyethyleneimine is dissolved in a solvent, and an isocyanate unsaturated compound solution is added dropwise under stirring and temperature control. The reaction is carried out after the addition is completed. After the reaction is completed, the photocrosslinking agent is obtained by distillation under reduced pressure.

[0015] The solvent is selected from one or a combination of two or more of acetone, tetrahydrofuran, ethyl acetate, DMF, and DMSO, preferably a mixed solvent of tetrahydrofuran and DMF in a volume ratio of 1:5-8. The temperature control is to control the temperature to 20-30°C, the dropwise addition is to be completed within 0.5-1 hour, the stirring speed is 200-500 r / min, the concentration of the isocyanate-unsaturated compound solution is 0.5-1 mol / L, and the solvent is selected from one or a combination of two or more of ethyl acetate, THF, and toluene. The reaction time is 36-48 hours.

[0016] The diglycidyl ether compound is selected from one or a combination of two or more of diglycidyl ether, hexanediol diglycidyl ether, ethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, bisphenol A diglycidyl ether, resorcinol diglycidyl ether, diethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, dipropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether, bisphenol A propoxylated diglycidyl ether, and 4,4-dihydroxy-3,3,5,5-tetramethyldiphenylmethane diglycidyl ether, and is preferably a combination of one or two of bisphenol F diglycidyl ether and bisphenol A diglycidyl ether.

[0017] The hydroxy acrylic acid derivative is selected from one or a combination of two or more of N-hydroxymethyl acrylamide, hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.

[0018] The soft monomer is selected from one or a combination of two or more of butyl acrylate, ethyl acrylate, n-octyl acrylate, isooctyl acrylate, isooctyl methacrylate, and dodecyl methacrylate.

[0019] The hard monomer is selected from one or a combination of two or more of methyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, vinyl acetate, and styrene.

[0020] The acrylate oligomer solution is prepared by a method comprising the following steps:

[0021] Under an inert atmosphere, the soft monomer, hard monomer, functional monomer, initiator and solvent are mixed evenly, the temperature is raised and kept constant for reaction, and after the reaction is completed, the temperature is lowered to room temperature and the solid content is adjusted to obtain an acrylate oligomer solution.

[0022] The initiator is used in an amount of 0.1-0.3 wt% of the total weight of the soft monomer, hard monomer, and functional monomer. The initiator is selected from one or a combination of two or more of azobisisobutyronitrile, azobisisoheptanenitrile, and dibenzoyl peroxide. The solvent is selected from one or a combination of two or more of ethyl acetate, butyl acetate, toluene, xylene, and acetone. The temperature is raised to 60-80°C, and the reaction time is 4-6 hours. The concentration is adjusted by evaporation or solvent addition to adjust the solid content. The solid content of the acrylate oligomer solution is 35-45 wt%.

[0023] The photoinitiator is selected from one or a combination of two or more of 1-hydroxycyclohexyl phenyl ketone, 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide, triaryl iodonium salt, and isopropylphenyl ferrocenyl hexaphosphate.

[0024] The raw materials of the UV viscosity-reducing adhesive layer further include 5-50 parts of an organic solvent, and the sum of the mass of the organic solvent and the solvent in the acrylate oligomer solution accounts for 40-60 wt % of the raw materials of the UV viscosity-reducing adhesive layer.

[0025] The organic solvent is selected from one or a combination of two or more of toluene, xylene, butanone, acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, and N,N-dimethylformamide.

[0026] The thickness of the UV viscosity-reducing adhesive layer is 15-35 μm; the thickness of the substrate layer is 70-150 μm; the material of the substrate layer is selected from one of PO film, PVC film, and PE film; the release film layer is a PET release film with a thickness of 25-50 μm.

[0027] The present invention also provides a method for preparing the heat-resistant wafer cutting protective film, comprising the following steps:

[0028] S1: Under light-proof conditions, the acrylate oligomer solution, the thermal curing agent, the photocrosslinking agent, the photoinitiator, and the organic solvent are uniformly mixed, allowed to stand, and defoamed to obtain the raw material for the UV viscosity-reducing adhesive layer;

[0029] S2: coating the raw material of the UV viscosity-reducing adhesive layer on the base material layer, baking to form the UV viscosity-reducing adhesive layer, and then compounding the release film layer on the UV viscosity-reducing adhesive layer and curing to obtain the above-mentioned heat-resistant wafer cutting protective film.

[0030] The coating method in step S2 includes knife coating. The coating temperature is 60-80°C. The baking temperature is 90-110°C for 2-5 minutes. The aging temperature is 25-60°C for 2-7 days.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention adds a heat-curing cross-linking agent to form a cross-linked network structure of acrylate oligomers, which then interpenetrates with another polymer network formed by photo-crosslinking agent after photocuring to form an interpenetrating network structure, thereby improving the heat resistance of the acrylate UV viscosity-reducing adhesive, reducing residual adhesive after cutting, making the peeling property easier to control, and at the same time having no adverse effect on the initial adhesion. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific embodiment, but is not limited to the content on the specification sheets. Unless otherwise specified, "parts" described in the embodiments of the present invention are all parts by weight. All reagents used are commercially available reagents in this area.

[0034] Hyperbranched polyethyleneimine was purchased from Nippon Shokubai, EPOMIN TM SP-003, amine value is 21mmol / g, of which the molar proportion of primary amine is 45%, the molar proportion of secondary amine is 35t%, the molar proportion of tertiary amine is 20%, and the number average molecular weight is 300g / mol;

[0035] EPOMIN TM SP-006, the amine value is 20 mmol / g, the molar proportion of primary amine is 35%, the molar proportion of secondary amine is 35%, the molar proportion of tertiary amine is 30%, and the number average molecular weight is 600 g / mol.

[0036] The PET release film was 50 μm thick and was purchased from Toray Industries, Ltd., Japan.

[0037] The PO film was 80 μm thick and was purchased from Toray Industries, Ltd., Japan.

[0038] Example 1

[0039] S1: Preparation of photocrosslinker: Under nitrogen atmosphere, 160 g of hyperbranched polyethyleneimine EPOMIN TM SP-006 was dissolved in 500 mL of a mixed solvent of tetrahydrofuran and DMF in a volume ratio of 1:5. The mixture was stirred and the temperature was controlled at 30°C. 1.288 L of a 1 mol / L 4-(maleimido)phenyl isocyanate solution (solvent: tetrahydrofuran) was added dropwise over 1 h. The reaction was allowed to proceed for 48 h. After the reaction, the solvent was removed by distillation under reduced pressure to obtain a photocrosslinker.

[0040] S2: Preparing an acrylate oligomer solution: Under a nitrogen atmosphere, 4000 g of butyl acrylate, 500 g of methyl methacrylate, 1500 g of hydroxyethyl acrylate, 18 g of azobisisobutyronitrile, and 9 L of ethyl acetate were mixed uniformly, heated to 80° C. and kept at this temperature for 6 h. After the reaction, the mixture was cooled to room temperature, and ethyl acetate was added to adjust the solid content to 42 wt %, to obtain an acrylate oligomer solution;

[0041] S3: Preparation of cutting protective film:

[0042] S31: Under light-shielding conditions, 1000 g of acrylate oligomer solution, 10 g of bisphenol A diglycidyl ether, 80 g of the photocrosslinker obtained in step S1, 15 g of 1-hydroxycyclohexyl phenyl ketone, and 207.5 g of acetone were mixed uniformly, allowed to stand, and defoamed to obtain a raw material for a UV-reducing adhesive layer;

[0043] S32: The UV anti-viscosity adhesive layer raw material obtained in step S31 is scraped onto the PO film at a temperature of 60°C, baked at 100°C for 5 minutes to form a UV anti-viscosity adhesive layer, and then a PET release film is compounded on the UV anti-viscosity adhesive layer, and aged at 60°C for 5 days to obtain a heat-resistant wafer cutting protective film with a 20μm thick UV anti-viscosity adhesive layer.

[0044] Example 2

[0045] The rest is the same as Example 1, except that in step S1, the amount of 4-(maleimido)phenyl isocyanate solution used is 1.12 L.

[0046] Example 3

[0047] The rest is the same as Example 1, except that in step S1, 118.5 g of hyperbranched polyethyleneimine EPOMIN TM SP-003 replaces 160g hyperbranched polyethyleneimine EPOMIN TM SP-006.

[0048] Example 4

[0049] The rest is the same as Example 1, except that in step S31, bisphenol A diglycidyl ether is replaced by bisphenol A propoxylated diglycidyl ether of equal mass.

[0050] Example 5

[0051] The rest is the same as Example 1, except that in step S1, an equal molar amount of methacryloyl isocyanate is used instead of 4-(maleimido)phenyl isocyanate.

[0052] Example 6

[0053] The rest is the same as Example 1, except that in S31, the amount of the photocrosslinking agent is 50 g, and the total solvent content in the raw materials of the UV viscosity-reducing adhesive layer is 40 wt%.

[0054] Example 7

[0055] S1: Preparation of photocrosslinker: Under nitrogen atmosphere, 160 g of hyperbranched polyethyleneimine EPOMIN TM SP-006 was dissolved in 500 mL of a mixed solvent of tetrahydrofuran and DMF in a volume ratio of 1:5. The mixture was stirred and the temperature was controlled at 30°C. 1.288 L of a 1 mol / L 4-(maleimido)phenyl isocyanate solution (solvent: tetrahydrofuran) was added dropwise over 1 h. The reaction was allowed to proceed for 48 h. After the reaction, the solvent was removed by distillation under reduced pressure to obtain a photocrosslinker.

[0056] S2: Preparing an acrylate oligomer solution: Under a nitrogen atmosphere, 2000 g of butyl acrylate, 200 g of methyl methacrylate, 1000 g of hydroxyethyl acrylate, 9 g of azobisisobutyronitrile, and 4.8 L of ethyl acetate were mixed uniformly, heated to 80° C. and kept at this temperature for 6 h. After the reaction, the temperature was cooled to room temperature and the solid content was adjusted to 42 wt % to obtain an acrylate oligomer solution;

[0057] S3: Preparation of cutting protective film:

[0058] In step S31, 1000 g of the acrylate oligomer solution, 5 g of bisphenol A diglycidyl ether, 50 g of the photocrosslinker obtained in step S1, 15 g of 1-hydroxycyclohexyl phenyl ketone, and 155 g of acetone were mixed under light-shielding conditions, allowed to stand, and defoamed to obtain a raw material for a UV-reducing adhesive layer.

[0059] S32: The UV anti-viscosity adhesive layer raw material obtained in step S31 is scraped onto the PO film at a temperature of 60°C, baked at 100°C for 5 minutes to form a UV anti-viscosity adhesive layer, and then a PET release film is compounded on the UV anti-viscosity adhesive layer, and matured at 60°C for 5 days to obtain the above-mentioned heat-resistant wafer cutting protective film with a 20μm thick UV anti-viscosity adhesive layer.

[0060] Comparative Example 1

[0061] The rest is the same as Example 1, except that bisphenol A diglycidyl ether is not added in step S31.

[0062] Comparative Example 2

[0063] The rest is the same as Example 1, except that the amount of the photocrosslinking agent in S31 is 40 g, and the total solvent content in the raw materials of the UV viscosity-reducing adhesive layer is 40 wt%.

[0064] Comparative Example 3

[0065] The rest is the same as Example 1, except that the amount of the photocrosslinking agent in S31 is 90 g, and the total solvent content in the raw materials of the UV viscosity-reducing adhesive layer is 40 wt%.

[0066] Comparative Example 4

[0067] The rest is the same as Example 1, except that in S31, the photocrosslinking agent is replaced by 1,4-butanediol diacrylate of equal mass.

[0068] The protective films prepared in the above examples and comparative examples were subjected to the following performance tests:

[0069] 1. 180° Peel Strength: Referring to the standard GB / T 2792-2014 test method for 180° peel strength of adhesives, affix the above protective film with a sample width of 25mm and a length of 200mm to a standard steel plate. Roll the sample back and forth twice with a 2kg standard roller. Place the sample at 23°C and 50% relative humidity for 2 hours. Then, test the peel strength before and after UV irradiation at a tensile rate of 300mm / min, and observe whether there is any residual adhesive. UV irradiation conditions: a 365nm wavelength UV lamp with a light power of 19mW / cm 2 Irradiate for 20 seconds.

[0070] 2. Heat resistance: Place the 180° peel strength sample in a 100°C oven for 6 hours of heat treatment using a 365nm wavelength UV lamp with a light power of 19mW / cm 2 After irradiation for 20 seconds, perform 180° peeling with a tensile rate of 300 mm / min and observe whether there is residual adhesive. The residual adhesive amount R is calculated by weighing the mass m0 of the standard steel plate, the mass m1 of the steel plate after adhesive film application, and the mass m2 of the steel plate with residual adhesive after peeling.

[0071]

[0072] 3. Initial tack: Tested in accordance with GB / T 4852-2002, Test method for initial tack of pressure-sensitive adhesive tapes (rolling ball method).

[0073] Table 1

[0074]

[0075]

[0076] It can be seen from Example 1, Example 6, and Comparative Examples 1-3 that the photocrosslinker has the effect of significantly reducing the pre-UV peeling force and initial adhesion, thereby reducing the effect of fixing the protective wafer. It is speculated that the photocrosslinker has a lubricating effect and can reduce the cohesive force of the UV viscosity-reducing adhesive layer. An appropriate amount of thermal curing agent not only has the effect of improving the initial adhesion performance, but also has the effect of significantly improving the pre-UV peeling force.

[0077] It can be seen from the heat resistance test results that the protective film prepared by the present invention has good resistance and controllable peeling performance.

[0078] The above detailed description is a specific description of one feasible embodiment of the present invention. This embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not depart from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A heat-resistant wafer cutting protective film, comprising a substrate layer, a UV adhesive layer, and a release film layer from bottom to top, characterized in that: The UV viscosity-reducing adhesive layer comprises the following raw materials in parts by weight: 100 parts of acrylate oligomer solution, 0.5-1 parts of thermal curing agent, 5-8 parts of photocrosslinking agent, and 0.5-1.5 parts of photoinitiator; the acrylate oligomer solution is prepared by solution polymerization of 20-40 parts of soft monomers, 2-5 parts of hard monomers, and 10-15 parts of hydroxy acrylic acid derivatives; the thermal curing agent is a diglycidyl ether compound; the photocrosslinking agent is prepared by the reaction of hyperbranched polyethyleneimine and an isocyanate-based unsaturated compound, and the molar ratio of the primary amine group on the hyperbranched polyethyleneimine to the isocyanate group on the isocyanate-based unsaturated compound is 1:1-1.

15.

2. The heat-resistant wafer cutting protective film according to claim 1, characterized in that: The solid content of the acrylate oligomer solution is 35-45 wt %.

3. The heat-resistant wafer cutting protective film according to claim 1, characterized in that: The isocyanate-based unsaturated compound is selected from one or a combination of two or more of 4-(maleimido)phenyl isocyanate, 3-isopropenyl-α,α-dimethylbenzyl isocyanate, methacryloyl isocyanate, and 2-isocyanoethyl acrylate, preferably 4-(maleimido)phenyl isocyanate.

4. The heat-resistant wafer cutting protection film according to claim 1, characterized in that: The hyperbranched polyethyleneimine has a number average molecular weight of 300-600 g / mol, an amine value of 18-21 mmol / g, wherein the molar proportion of primary amine is 35-45%, the molar proportion of secondary amine is 20-35%, and the molar proportion of tertiary amine is 20-35%.

5. The heat-resistant wafer cutting protection film according to claim 1, characterized in that: The photocrosslinking agent is prepared by a method comprising the following steps: Under an inert atmosphere, hyperbranched polyethyleneimine is dissolved in a solvent, and an isocyanate-based unsaturated compound solution is added dropwise under stirring and temperature control conditions. After the addition, a reaction is carried out, and after the reaction is completed, reduced pressure distillation is performed to obtain a photocrosslinking agent.

6. The heat-resistant wafer cutting protection film according to claim 5, characterized in that: The temperature control is to control the temperature to 20-30°C, the dripping is to be completed within 0.5-1h, the stirring speed is 200-500r / min; the concentration of the isocyanate unsaturated compound solution is 0.5-1mol / L, and the solvent is selected from one or a combination of two or more of ethyl acetate, THF, and toluene; and the reaction time is 36-48h.

7. The heat-resistant wafer cutting protection film according to claim 1, characterized in that: The diglycidyl ether compound is selected from one or a combination of two or more of diglycidyl ether, hexanediol diglycidyl ether, ethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, bisphenol A diglycidyl ether, resorcinol diglycidyl ether, diethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, dipropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether, bisphenol A propoxylated diglycidyl ether, and 4,4-dihydroxy-3,3,5,5-tetramethyldiphenylmethane diglycidyl ether; preferably, a combination of one or two of bisphenol F diglycidyl ether and bisphenol A diglycidyl ether.

8. The heat-resistant wafer cutting protection film according to claim 1, characterized in that: The hydroxy acrylic acid derivative is selected from one or a combination of two or more of N-hydroxymethyl acrylamide, hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate; the soft monomer is selected from one or a combination of two or more of butyl acrylate, ethyl acrylate, n-octyl acrylate, isooctyl acrylate, isooctyl methacrylate, and dodecyl methacrylate; the hard monomer is selected from one or a combination of two or more of methyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, vinyl acetate, and styrene.

9. The heat-resistant wafer cutting protection film according to claim 1, characterized in that: The acrylate oligomer solution is prepared by a method comprising the following steps: Under an inert atmosphere, the soft monomer, hard monomer, functional monomer, initiator and solvent are uniformly mixed, the temperature is raised and kept constant for reaction, and after the reaction is completed, the temperature is lowered to room temperature, and the solid content is adjusted to obtain an acrylate oligomer solution.

10. The method for preparing the heat-resistant wafer cutting protective film according to any one of claims 1 to 9, characterized in that: The steps include: S1, in a light-proof condition, uniformly mixing the acrylate oligomer solution, the thermal curing agent, the photocrosslinking agent, the photoinitiator, and the organic solvent, standing and defoaming, to obtain the raw material of the UV viscosity-reducing adhesive layer; S2: coating the raw material of the UV anti-viscosity adhesive layer on the substrate layer, baking to form the UV anti-viscosity adhesive layer, and then compounding the release film layer on the UV anti-viscosity adhesive layer, and ripening to obtain the above-mentioned heat-resistant wafer cutting protective film.